The effects of experimentally induced hyperthyroidism on the diving physiology of harbor seals (Phoca vitulina) - Weingartner, Gundula M.; Thornton, Sheila J.; Andrews, Russel D.; Enstipp, Manfred R.; Dorota Barts, Agnieszka; Hochachka, Peter W. (Frontiers in Physiology, 2012)
Many phocid seals are expert divers that remain submerged longer than expected based on estimates of oxygen storage and utilization. This discrepancy is most likely due to an overestimation of diving metabolic rate. During diving, a selective redistribution of blood flow occurs, which may result in reduced metabolism in the hypoperfused tissues and a possible decline in whole-body metabolism to below the resting level (hypometabolism). Thyroid hormones are crucial in regulation of energy metabolism in vertebrates and therefore their control might be an important part of achieving a hypometabolic state during diving. To investigate the effect of thyroid hormones on diving physiology of phocid seals, we measured oxygen consumption, heart rate, and post-dive lactate concentrations in five harbor seals (Phoca vitulina) conducting 5 min dives on command, in both euthyroid and experimentally induced hyperthyroid states. Oxygen consumption during diving was significantly reduced (by 25 %) in both euthyroid and hyperthyroid states, confirming that metabolic rate during diving falls below resting levels. Hyperthyroidism increased oxygen consumption (by 7-8 %) when resting in water and during diving, compared with the euthyroid state, illustrating the marked effect of thyroid hormones on metabolic rate. Consequently, post-dive lactate concentrations were significantly increased in the hyperthyroid state, suggesting that the greater oxygen consumption rates forced seals to make increased use of anaerobic metabolic pathways. During diving, hyperthyroid seals also exhibited a more profound decline in heart rate than seals in the euthyroid state, indicating that these seals were pushed towards their aerobic limit and required a more pronounced cardiovascular response. Our results demonstrate the powerful role of thyroid hormones in metabolic regulation and support the hypothesis that thyroid hormones play a role in modulating the at-sea metabolism of phocid seals.